2016
DOI: 10.7567/jjap.55.08nb12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fe coating of nucleation sites on epitaxial growth of Fe oxide nanocrystals on Si substrates

Abstract: We studied the effect of Fe coating on the epitaxial growth of Fe3O4 nanocrystals (NCs) over Fe-coated Ge epitaxial nuclei on Si(111). To completely cover Ge nuclei with Fe, some amount of Fe (>8 monolayers) must be deposited. Such covering is a key to epitaxial growth because an Fe coating layer prevents the oxidation of Ge surfaces during Fe3O4 formation, resulting in the epitaxial growth of Fe3O4 on them. This study demonstrates that an appropriate Fe coating of nucleation sites leads to the epitaxial gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…The full width at half maximum (FWHM) values of the 224 Fe3O4 fitted peaks in Fe 3 O 4 NCs on Ge nuclei with Fe coating layers of 6, 15, and 30 MLs were 5.5, 4.7, and 3.9 nm −1 , respectively (Figure 2(d) and Supplemental Material 1), indicating that the crystallinity is enhanced with increasing the deposition amount of Fe coating layer. This trend is similar to the previously reported result in Fe 3 O 4 NCs on Ge nuclei formed by Fe deposition at high temperature [29], where it was reported that the oxidation of Ge nucleus surface at the first stage of Fe 3 O 4 growth was prevented by Fe coating, resulting in the higher crystallinity of Fe 3 O 4 . Therein, at the final stage of Fe 3 O 4 growth or after exposure to oxygen atmosphere, the GeO x was inserted at the Fe 3 O 4 /Ge interface [30].…”
Section: Resistive Switching Characteristics In the Ncs Grown At Rtsupporting
confidence: 92%
“…The full width at half maximum (FWHM) values of the 224 Fe3O4 fitted peaks in Fe 3 O 4 NCs on Ge nuclei with Fe coating layers of 6, 15, and 30 MLs were 5.5, 4.7, and 3.9 nm −1 , respectively (Figure 2(d) and Supplemental Material 1), indicating that the crystallinity is enhanced with increasing the deposition amount of Fe coating layer. This trend is similar to the previously reported result in Fe 3 O 4 NCs on Ge nuclei formed by Fe deposition at high temperature [29], where it was reported that the oxidation of Ge nucleus surface at the first stage of Fe 3 O 4 growth was prevented by Fe coating, resulting in the higher crystallinity of Fe 3 O 4 . Therein, at the final stage of Fe 3 O 4 growth or after exposure to oxygen atmosphere, the GeO x was inserted at the Fe 3 O 4 /Ge interface [30].…”
Section: Resistive Switching Characteristics In the Ncs Grown At Rtsupporting
confidence: 92%
“…Subsequently deposited Ge atoms were trapped at these nanowindows to form Ge NCs with high areal density. [26][27][28][29][30] ZnO was deposited on the Ge NCs on Si to form NC seed layers, followed by NW growth. ZnO deposition for seed layers and NW growth were conducted under the same conditions as the case of conventional seed layers.…”
Section: Experimental Methodsmentioning
confidence: 99%